Leveraging online selling through social media influencers - Shuqair, Saleh (2023)
Shuqair, S., Filieri, R., Viglia, G., Mattila, A. S., & Pinto, D. C. (2024). Leveraging online selling through social media influencers. Journal of Business Research, 171(January), 1-10. [114391]. https://doi.org/10.1016/j.jbusres.2023.114391 --- %ABS3%